An introduction to object-oriented programming with Java - Wu, C. Thomas (Boston, Massachusetts : McGraw Hill Education, 2010)
An Introduction to Object-Oriented Programming with Java takes a full-immersion approach to object-oriented programming. Proper object-oriented design practices are emphasized throughout the book. Students learn how to use the standard classes first, then learn to design their own classes. Wu uses a gentler approach to teaching students how to design their own classes, separating the coverage into two chapters. GUI coverage is also located independently in the back of the book and can be covered if desired. Wu also features a robust set of instructors' materials including PowerPoint slides, code samples, and quiz questions.
Introduction to computers and programming languages -- Introduction to object-oriented programming and software development -- Getting started with Java -- Numerical data -- Defining your own classes: part 1 -- Selection statements -- Repetition statements -- Defining your own classes: part 2 -- Exceptions and assertions -- Characters and strings -- Arrays and collections -- Sorting and searching -- File input and output -- Inheritance and polymorphism -- GUI and event-driven programming -- Recursive algorithms -- Appendix A: How to run Java programs -- Appendix B: Sample programs -- Appendix C: Standard classes and interfaces -- Appendix D: UML diagrams -- Index.
Includes index.
Keywords: OBJECT-ORIENTED PROGRAMMING (COMPUTER SCIENCE)